Operations research (OR) models for improving traffic signal timing mechanisms - Teo, Yu An. (2012)
This project focuses on the development of an optimization model to obtain the optimal traffic signal timing plan for a 4-way intersection. We begin by showcasing current studies for the optimization of traffic signal timing system and existing methods for minimizing delay and maximizing capacity.